The protection of human health against free trade of goods in the Andean Community - Reyes Tagle, Yovana (2019)
Article 73 of the Cartagena Agreement recognizes that the protection of human life and health can be justified through the adoption of import restrictions in the Andean Community. This paper analyzes the suitability between the national measure adopted and the objective pursued. The quantitative restrictions introduced by Ecuador to reduce the emission of greenhouse gases to protect human health and their justification in the light of the Cartagena Agreement are used as a case study. The paper argues that the analysis of an import restriction adopted to protect human health does not only require a quantitative assessment of thev contribution of the restriction to achieve the desired objective; namely, that the sector or activity that causes the problem is the most significant. A qualitative approach is necessary.